Clinical and Radiologic Disease Activity in Pregnancy and Postpartum in MS. Issue 2 (12th March 2021) - Anderson, Annika; Krysko, Kristen M.; Rutatangwa, Alice; Krishnakumar, Tanya; Chen, Chelsea; Rowles, William; Zhao, Chao; Houtchens, Maria K.; Bove, Riley
Abstract : Objective: To evaluate radiologic and clinical inflammatory activity in women with MS during pregnancy and postpartum. Methods: We performed a retrospective analysis of prospectively collected clinical and MRI reports for women who became pregnant while followed at the University of California, San Francisco MS Center between 2005 and 2018. Proportion of brain MRIs with new T2-hyperintense or gadolinium enhancing (Gd+) lesions (primary outcome) and annualized relapse rate (ARR; secondary) were compared before and after pregnancy. Results: We identified 155 pregnancies in 119 women (median Expanded Disability Status Scale [EDSS] 2.0). For the 146 live birth pregnancies, prepregnancy ARR was 0.33; ARR decreased during pregnancy, particularly the third trimester (ARR 0.10, p = 0.017) and increased in the 3 months postpartum (ARR 0.61, p = 0.012); and 16% of women experienced a clinically meaningful increase in EDSS. Among 70 pregnancies with paired brain MRIs available, 53% had new T2 and/or Gd+ lesions postpartum compared with 32% prepregnancy ( p < 0.001). Postpartum clinical relapses were associated with Gd+ lesions ( p < 0.001). However, even for patients without postpartum relapses, surveillance brain MRIs revealed new T2 and/or Gd+ lesions in 31%. Protective effects of exclusive breastfeeding for ≥3 months (odds ratio = 0.3, 95% confidence interval 0.1–0.9) were observed for relapses. Conclusions: Building on previous reports of increased relapse rate in the first 3 months postpartum, we report a significant association between inflammation on MRI and this clinical activity. We also detected postpartum radiologic activity in the absence of relapses. Both clinical and radiologic reassessment may inform optimal treatment decision-making during the high-risk early postpartum period.